Nitrate Occurrence in Groundwater: A Case Study from Haryana - Prem, Guru; Jhorar, Raj Kumar; Miegel, Konrad; Mittal, S B (Journal of Agricultural Engineering, 2008)
Groundwater and soil samples were collected to determine NO³? and N levels at different locations in two villages and to investigate probable reasons for the occurrence of high nitrate concentration in groundwater. The soil of the study area was loamy sand throughout the profile up to 15 m except sandy loam at depth of 8.1 to 10.8 m. All the groundwater samples collected during different time periods (pre-monsoon and post-monsoon) showed nitrate concentration of about more than twice the maximum acceptable nitrate concentration for drinking water standards (45 mg L?¹). Water quality with respect to nitrate concentration in the pumped groundwater was determined for different pumping rates and time periods after the start of pumping. The nitrate concentration did not change considerably with the discharge and time during the pumping. Lower nitrate concentration (1.44 me L?¹) in groundwater was observed at shallow depth (5.45- 8.1 m) as compared to 1.56 me L?¹ in relatively deep (10.8 to 15 m) groundwater. Total nitrogen content in subsurface profile to a depth of 15 m was found to vary from 0.13 to 0.18%. Wide variation in nitrate content (56.19 to 91.36 mg L?¹) was observed among tubewell water of two contiguous villages.